Integration of satisfaction and quality of recovery. Issue 3 (September 2018) - Bruder, Nicolas; Auquier, Pascal
Abstract : Among patient-reported outcomes, patient satisfaction and quality of recovery are key measures of patient-centred care. The measurement of patient satisfaction should use validated, multidimensional scales. There are general scales that aim to evaluate the entire perioperative period and scales focused on specific periods (post-operative) or techniques (loco-regional anaesthesia). Recovery assessment tools (such as the PostopQRS) share some domains with satisfaction scales and also have major differences by construction. As such, recovery and satisfaction scales are complementary. Because there is no reference value of patient satisfaction, the scales are used to compare two management strategies or to follow similar populations of patients with time. Improving patient satisfaction goes beyond quality improvement. In a large database, the highest satisfaction was associated with the lowest morbidity and mortality. Thus, it is likely that the process of improving quality changes multiple components of medical management, hence improving several patient outcomes.